Popular geographies: celebrating the nation in Canadian Geographic, Australian Geographic and New Zealand Geographic, 1995-2004 : a thesis presented in partial fulfilment of the requirements for the degree of Master of Arts in Geography at Massey University, Palmerston North, New Zealand - Wilson, Andrew Charles Bruce (Massey University, 2008)
Popular geography magazines like National Geographic (NG) provide readers with a lens of the world around them. Yet sadly they often only serve a limited utilitarian purpose as dust collectors on coffee tables of hospital waiting rooms or doctors’ practices. It should be of little surprise then that the relative importance of geographic magazines as a representational forum has been underestimated historically. The importance of geographic magazines as an outlet for creating and disseminating preconceived visions of what may be termed ‘popular geographies’ has only become the subject of scrutiny in the last two decades. Authors including Lutz and Collins (1993) and Rothenberg (1994, 2007) have reflected critically upon the place of NG as a powerful ideological institution for legitimating particular visions of the world in the wider corpus of the discipline of geography. Yet while there has been a substantial volume of work dedicated to unravelling the situated lens of NG there has been no research devoted to deciphering the lenses of other geography magazines such as Canadian Geographic (CG), Australian Geographic (AG) or New Zealand Geographic (NZG). These magazines also embody the ideals of adventure, discovery and nature made famous by NG but purvey geography through distinctively national narratives. Through discourse analysis the thesis examines these three magazines in order to unravel geographic imaginations of nationalism in CG, AG and NZG and in the process challenge divergent conceptions of geography itself as both an academic discipline and popular subject.
Keywords: Popular geography; Imaginative geographies; Geography magazines; National geography; Fields of Research::260000 Earth Sciences::269900 Other Earth Sciences::269901 Physical geography